(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Strategic communication is an essential aspect in managing modern armed conflict. Through the analysis of the war in Afghanistan (2001-2011), this study aims to investigate if we are faced with a radical transformation of previous approaches or a change in the culture of its operations. The change made by the General Stanley McChrystal, upon taking control of the supreme command of the ISAF (International Security Assistance Force) operations, in June 2009, represents a development that had already been initiated by general Petraeus in Iraq. The tactics adopted before by France in Algeria in turn inspired these. In November 2010, NATO included this new method of dealing with peace operations as a new Strategic Concept, as part of its Comprehensive Approach. To conclude, this paper discusses the various definitions of strategic communication and proposes a revised definition of this concept